Total synthesis of (-)-tetrazomine and biochemical studies - Scott, Jack David, author; Williams, Robert M., advisor (Colorado State University. Libraries, 2001)
The total synthesis of (-)-tetrazomine is presented in which the relative and absolute stereochemistry of the natural product has been determined. The synthesis features a unique iminium cyclization followed by a 1,3-dipolar cylcoaddition. The stereochemistry of advance intermediates were determined by extensive 2D NMR techniques. The asymmetric synthesis of all four stereoisomers of β-hydroxy pipecolic acid has also been described. These stereoisomers were compared to the amino acid isolated from the hydrolysis of tetrazomine to determine the absolute stereochemistry of the amino acid moiety on the natural product. The route used to complete the total synthesis allowed for pipecolic acid analogs to be synthesized in order to study the effect of structure on the biochemical characteristics of these compounds. Along with oxazolidine ring containing analogs, ring opened amino nitrile analogs were also studied.
Keywords: Tetrazomine